Factors Related to Compliance with Antiretroviral Consumption in HIV/AIDS Patients in Makassar City - GobelFatmah Afrianty; Andayanie, Ella; Sukmawati, Sukmawati; Darlis, Idhar (Window of Health : Jurnal Kesehatan, 2023)
The management of HIV/AIDS with ARV therapy is largely determined by the adherence to PLHIV in consuming ARVs, WHO in 2021 reported that AIDS-related deaths have decreased globally thanks to the use of ARV therapy of 650,000 people living with HIV 68% fewer died from HIV, compared to the peak the number of cases was in 2004, and 52% less than in 2010. People with HIV who are not compliant with taking ARVs either in doses or shifting the time of taking their medication will cause drug resistance, increase in the amount of virus in the body, increase the risk of transmission, decrease the quality of life of PLHIV because it will cause various opportunistic infections. This study aims to analyze factors related to antiretroviral therapy adherence of people living with HIV/AIDS in Makassar City. The research method used is observational research with a cross-sectional study approach. The population and sample were PLWHA who went to hospitals and were under the guidance of HIV/AIDS NGOs. The sample was taken purposively with certain criteria with a total of 80 PLWHA. The results showed that out of 80 PLHIV, 51 PLHIV (63.8%) adhered to taking ARVs with a value of 0.000 ≤ α 0.005, meaning that social support was related to adherence to ARV therapy, while knowledge was not related to adherence to ARV therapy, pValue 0.598 > α 0.05, however if seen from the proportion of 58 PLWHA with sufficient knowledge, 37 PLHIV (46.3%) adhered to ARV therapy. It is recommended for PLWHA to be more open about their disease status and involve HIV NGOs to educate their families and people in their surrounding environment about HIV to reduce stigma and discrimination so that PLWHA can freely seek treatment and get support from their social environment to carry out perfect treatment and improve their quality of life.